Anthropological (in)fidelities to Alain Badiou. (June 2019) - Jansen, Stef
This article constructs a dialogue between Alain Badiou's philosophy of evental subjectivation and anthropology as an empirical social science. Elaborating on the few existing anthropological engagements with Badiou's theory by bringing in his more recent writing, it aims to familiarise anthropologists with some key dimensions of his approach and conceptual apparatus and to consider its use for anthropological theorisation of political struggle and process. Reflecting ethnographically on the (after)life of one happening in Bosnia and Herzegovina (the 2014 Winter Revolt) in light of another happening (the 1992–1995 war), I investigate the conditions under which happenings may or may not come to function—and be recognised—as events, as catalysts of change. Substantially departing from Badiou's normative-universalist approach, I nevertheless argue that a core dimension of his project—an effort to conceptualise subject formation processually in relation to events—can inspire interesting avenues for anthropological theorising. Particularly in addressing questions of perspective, intensity and duration, I contend that anthropologists are well-placed to trace modalities of what Badiou calls 'fidelity' and its refusal.